The neurohormonal basis of pulmonary hypertension in heart failure with preserved ejection fraction - Obokata, Masaru; Kane, Garvan C; Reddy, Yogesh N V; Melenovsky, Vojtech; Olson, Thomas P; Jarolim, Petr; Borlaug, Barry A (European heart journal, 2019)
AIMS: Pulmonary hypertension (PH) represents an important phenotype among the broader spectrum of patients with heart failure with preserved ejection fraction (HFpEF), but its mechanistic basis remains unclear. We hypothesized that activation of endothelin and adrenomedullin, two counterregulatory pathways important in the pathophysiology of PH, would be greater in HFpEF patients with worsening PH, and would correlate with the severity of haemodynamic derangements and limitations in aerobic capacity and cardiopulmonary reserve. METHODS AND RESULTS: Plasma levels of C-terminal pro-endothelin-1 (CT-proET-1) and mid-regional pro-adrenomedullin (MR-proADM), central haemodynamics, echocardiography, and oxygen consumption (VO2) were measured at rest and during exercise in subjects with invasively-verified HFpEF (n = 38) and controls free of HF (n = 20) as part of a prospective study. Plasma levels of CT-proET-1 and MR-proADM were highly correlated with one another (r = 0.89, P < 0.0001), and compared to controls, subjects with HFpEF displayed higher levels of each neurohormone at rest and during exercise. C-terminal pro-endothelin-1 and MR-proADM levels were strongly correlated with mean pulmonary artery (PA) pressure (r = 0.73 and 0.65, both P < 0.0001) and pulmonary capillary wedge pressure (r = 0.67 and r = 0.62, both P < 0.0001) and inversely correlated with PA compliance (r = -0.52 and -0.43, both P < 0.001). As compared to controls, subjects with HFpEF displayed right ventricular (RV) reserve limitation, evidenced by less increases in RV s' and e' tissue velocities, during exercise. Baseline CT-proET-1 and MR-proADM levels were correlated with worse RV diastolic reserve (ΔRV e', r = -0.59 and -0.67, both P < 0.001), reduced cardiac output responses to exercise (r = -0.59 and -0.61, both P < 0.0001), and more severely impaired peak VO2 (r = -0.60 and -0.67, both P < 0.0001). CONCLUSION: Subjects with HFpEF display activation of the endothelin and adrenomedullin neurohormonal pathways, the magnitude of which is associated with pulmonary haemodynamic derangements, limitations in RV functional reserve, reduced cardiac output, and more profoundly impaired exercise capacity in HFpEF. Further study is required to evaluate for causal relationships and determine if therapies targeting these counterregulatory pathways can improve outcomes in patients with the HFpEF-PH phenotype. CLINICAL TRIAL REGISTRATION: NCT01418248; https://clinicaltrials.gov/ct2/results? term=NCT01418248&Search=Search.
Keywords: tepový objem; Endothelin-1; Biomarker; Humans; Case-Control Studies; Heart failure; Heart Failure; Stroke Volume; srdeční selhání; lidé středního věku; echokardiografie; studie případů a kontrol; Oxygen Consumption; Pulmonary circulation; Echocardiography; Female; Aged; tolerance zátěže; Atrial Natriuretic Factor; endotelin-1; senioři; lidé; Hypertension, Pulmonary; Peptide Fragments; plicní hypertenze; arteriální tlak; ženské pohlaví; Male; Middle Aged; atriální natriuretický faktor; spotřeba kyslíku; peptidové fragmenty; Cross-Sectional Studies; Arterial Pressure; Exercise Tolerance; Exercise; hemodynamika; arteria pulmonalis; mužské pohlaví; prospektivní studie; cvičení; Hemodynamics; průřezové studie; Pulmonary Artery; Prospective Studies